The twenty first century art book - Griffin, Jonathan (London : Phaidon Press Limited, 2014)
A complement to the landmark The Art Book, The 21st-Century Art Book is an accessible guide to best contemporary art made since 2000. Showcasing over 280 artists in alphabetical order, it place established figures like Jeff Wall, Marlene Dumas and Maurizio Cattelan alongside the rising stars of the next generation such as Camille Henrot and Haroon Mirza. International in outlook, it draws together artists from every continent and documents the unprecedented variety of approaches and mediums used by today's artists - from oil paintings and bronze sculptures to video installations and performance. Each artist is represented by a full-page colour plate and an illuminating text that both explains the work and introduces its creator. Easy to use, with an international directory of biennials and art fairs where the reader can encounter the art face to face.
Keywords: Art, Modern -- 21st century -- Dictionaries; Artists -- Dictionaries